Plastic breeze: Volatile organic compounds (VOCs) emitted by degrading macro- and microplastics analyzed by selected ion flow-tube mass spectrometry. (May 2021) - La Nasa, Jacopo; Lomonaco, Tommaso; Manco, Enrico; Ceccarini, Alessio; Fuoco, Roger; Corti, Andrea; Modugno, Francesca; Castelvetro, Valter; Degano, Ilaria
Abstract: Pollution from microplastics (MPs) has become one of the most relevant topics in environmental chemistry. The risks related to MPs include their capability to adsorb toxic and harmful molecular species, and to release additives and degradation products into ecosystems. Their role as a primary source of a broad range of harmful volatile organic compounds (VOCs) has also been recently reported. In this work, we applied a non-destructive approach based on selected-ion flow tube mass spectrometry (SIFT-MS) for the characterization of VOCs released from a set of plastic debris collected from a sandy beach in northern Tuscany. The interpretation of the individual SIFT-MS spectra, aided by principal component data analysis, allowed us to relate the aged polymeric materials that make up the plastic debris (polyethylene, polypropylene, and polyethylene terephthalate) to their VOC emission profile, degradation level, and sampling site. The study proves the potential of SIFT-MS application in the field, as a major advance to obtain fast and reliable information on the VOCs emitted from microplastics. The possibility to obtain qualitative and quantitative data on plastic debris in less than 2 min also makes SIFT-MS a useful and innovative tool for future monitoring campaigns involving statistically significant sets of environmental samples. Graphical abstract: Image 1 Highlights: VOCs released from plastic debris were analyzed non-destructively by SIFT-MS. Aged polymeric materials were characterized based on their SIFT-MS spectra. PCA analysis of spectra correlated VOC profile, degradation level and sampling site. SIFT-MS provided fast and reliable information on the VOCs emitted by microplastics.